Potential of Animal Production Integrated to The Palm Oil Estate as an Agribusiness Base on Ruminant - Batubara, Leo P (Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
Palm oil estates is very large in Indonesia, predominantly in North Sumatera, Riau and South Sumatera provinces. The production of by-products such as palm oil leaf (POL); palm oil fronds (POF); solid ex decanter Â (SED) and palm kernel cake (PKC) are 17,1 tons; 486 tons; 840â1260 kgs; 567 kgs in dried form per-hectar per-year respectively. A number of research showed that the utilization of these by-products are potential as energy and protein source for cattle and sheep and can reduce 20-40% of feeding cost compared to conventional concentrate diet. According to 70â80% of total production cost are feed cost, there fore using these by-products give an agreat opportunity to integrate the animal production with palm estate as an agribisnis scale. The plantation area that have an oil palm industry is the main opportunity for establishing the integration production system. The feed industry can be run efficiently, because by-products can be supplied by oil industry directly.Â  Key words: Integration, palm oil, livestock, by-products